RUSSIAN PHYSICIANS AND SCIENTISTS HAVE AGREED TO JOINTLY CONTROL AUTOIMMUNE DISEASES: ACCORDING TO THE PROCEEDINGS OF THE FIRST INTERDISCIPLINARY CONFERENCE ON AUTOIMMUNE AND IMMUNODEFICIENCY DISEASES - A. S. Avdeeva (Научно-практическая ревматология)
.